380 Left heart disease phenotype and use of pulmonary vasodilators in elderly patients with pulmonary arterial hypertension: the Patriarca registry. (8th December 2021) - Toma, Matteo; Miceli, Roberta; Bonsante, Edoardo; Confalonieri, Marco; Garascia, Andrea; Ghio, Stefano; Lattanzio, Mariangela; Lombardi, Carlo Mario; Paciocco, Giuseppe; Piccinino, Cristina; Rota, Irene; Scelsi, Laura; et al.
Abstract: Aims: The prevalence of occult left heart disease (LHD) and the feasibility of vasodilator therapy in the progressively growing population of elderly subjects with pulmonary arterial hypertension (PAH) are under scrutiny. We evaluated the presence of a LHD phenotype and the patterns of vasodilator treatment in such patients. Methods and results: The PATRIARCA registry collected cross-sectional data from 180 subjects with PAH or chronic thromboembolic pulmonary hypertension and ≥70 years of age in 11 Italian centres between 1 December 2019 and 15 September 2020. After excluding patients with CTEPH or incomplete follow-up haemodynamic parameters, 77 individuals with PAH diagnosed at ≥ 65 years of age according to current guidelines were included in the analysis. A LHD phenotype was defined as follows, expanding the criteria adopted in the AMBITION trial: (i) ≥3 among body mass index ≥30 kg/m 2, systemic hypertension, diabetes, and significant coronary artery disease; (ii) 2 of the risk factors for LHD above and ≥1 among permanent atrial fibrillation, left ventricular (LV) hypertrophy, LV ejection fraction <50%, at least moderate mitral or aortic valve disease, and left atrial dilation; (iii) pulmonary vascular resistance (PVR) between 3 and 3.75 WU or PVR between 3.75 and 6.25 WU in the presence of a pulmonary artery wedge pressure (PAWP) of 13–15 mmHg. Forty-one (53%) patients had a LHD phenotype according to the most recent clinical and haemodynamic evaluation, which was performed 16 (4–35) months after diagnosis (Figure). As per definition, they had higher rates of comorbidities and more often echocardiographic signs of LHD (not shown). The frequency of NYHA classes I–II was comparable between the two groups, while the 6 min-walking distance tended to be lower in subjects with a LHD phenotype than in those without (Figure, left panel). Furthermore, these latter had lower PVR and higher PAWP. No differences were seen in treatment with pulmonary vasodilators, with around 50% of patients receiving double oral combination therapy in both groups (Figure, right panel). During the study period, 7 (17%) and 4 (11%) patients died in the LHD and no-LHD groups, respectively ( P = 0.40). Conclusions: In this real-world cohort of elderly patients, a LHD phenotype was common despite an initial haemodynamic diagnosis of PAH. However, it did not appear to cause simplification or discontinuation of pulmonary vasodilator therapy. Longitudinal studies are needed to determine whether and how a LHD phenotype affects the use and effects of PAH drugs in the elderly.